2021
DOI: 10.17718/tojde.1002776
|View full text |Cite
|
Sign up to set email alerts
|

Critical Factors Influencing Moocs Retention: The Mediating Role of Information Technology

Abstract: In the current digital era, Massive Open Online Courses (MOOCs) are considered as an educational revolution specifically in the current situation of COVID-19. Although students from all over the globe register for MOOCs, only a small proportion of participants complete the online courses. MOOCs at present encounter the problem of low retention rates, thus providing numerous research gaps. This paper investigates the impact of critical factors such as the instructor's role, course relevancy, learning outcomes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…In MOOCs, the course factors affect a learner's motivation to learn. With an appealing course, learners are more willing and motivated to continue learning (Khan et al, 2021). The interactivity of the course content also aids to increase a learner's continuance intention, and heightens learning enthusiasm and engagement (Deshpande and Chukhlomin, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In MOOCs, the course factors affect a learner's motivation to learn. With an appealing course, learners are more willing and motivated to continue learning (Khan et al, 2021). The interactivity of the course content also aids to increase a learner's continuance intention, and heightens learning enthusiasm and engagement (Deshpande and Chukhlomin, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the interaction between learners can reduce loneliness and increase satisfaction, thus promoting the continuance intention (Ma et al, 2022). The interaction between instructors and learners directly affects a learner's motivation to complete the course (Khan et al, 2021). When the instructor provides good feedback to the learners, a two-way channel between the instructor and the learners is formed, rather than the traditional one-way communication.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations